The Psychological Well-Being in Building Resilience of Indonesian Muslim Families: A Study of Hussein Muhammad's Thought - Anisa, Lina Nur (De Jure: Jurnal Hukum dan Syari'ah, 2023)
The relationship between husband and wife in the household is strongly influenced by the socio-cultural conditions of a society. In Indonesia, there are still many facts of life in husband-wife relationships that are still dominated by men in most aspects of life, both the distribution of rights and obligations as well as the authority and involvement of the parties in determining important family steps and decisions. This is because the culture in Indonesia is built on an unbalanced or unequal order in which men are placed as superior parties over inferior women. Husein Muhammad’s thinking can place the issue of husband-wife relations in a balanced and fair manner with all the variations of interpretation from century to century, from one hadith to another, and from one interpreter to another. His notion is also undoubtedly relevant to the concept of psychological well-being, which states that for a person to bring out their best potential, a person must be psychologically well, and one of the aspects that can affect psychological well-being is the pattern of relationships in the family. So, a balanced and fair relationship pattern will bring out the best potential in the family.